2012
DOI: 10.1371/journal.pone.0049430
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Free Delivery Care on Health Facility Delivery and Insurance Coverage in Ghana’s Brong Ahafo Region

Abstract: BackgroundMany sub-Saharan countries, including Ghana, have introduced policies to provide free medical care to pregnant women. The impact of these policies, particularly on access to health services among the poor, has not been evaluated using rigorous methods, and so the empirical basis for defending these policies is weak. In Ghana, a recent report also cast doubt on the current mechanism of delivering free care – the National Health Insurance Scheme. Longitudinal surveillance data from two randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
130
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(141 citation statements)
references
References 23 publications
8
130
0
3
Order By: Relevance
“…The basis for the above ratings included; attitude of staff, waiting time, availability of medicines at the facilities, physical examination by clinicians. This finding is in line with those of (Dzakpasu et al, 2012;MoH, 2007;Fusheini et al, 2012) who identified that patient satisfaction with the quality of health care in NHIS-accredited health facilities remains low especially with regard to staff attitudes and long waiting times, differential treatment for NHIS-insured and non-NHIS insured clients, quality of drugs covered by the NHIS, and limited client/community engagement in NHIS activities. It is of the view of the authors that this practice could erode confidence in the operation of the scheme thereby affecting (re) enrolment and hence demand for health service.…”
Section: Assessment Of Subscribers' Overall Level Of Satisfaction Of supporting
confidence: 86%
“…The basis for the above ratings included; attitude of staff, waiting time, availability of medicines at the facilities, physical examination by clinicians. This finding is in line with those of (Dzakpasu et al, 2012;MoH, 2007;Fusheini et al, 2012) who identified that patient satisfaction with the quality of health care in NHIS-accredited health facilities remains low especially with regard to staff attitudes and long waiting times, differential treatment for NHIS-insured and non-NHIS insured clients, quality of drugs covered by the NHIS, and limited client/community engagement in NHIS activities. It is of the view of the authors that this practice could erode confidence in the operation of the scheme thereby affecting (re) enrolment and hence demand for health service.…”
Section: Assessment Of Subscribers' Overall Level Of Satisfaction Of supporting
confidence: 86%
“…Hospitals have reported increased overcrowding at maternity wards for instance Kenyatta National Hospital in May 2013 reported 938 deliveries as compared to 1375 in May 2014 this increase was occasioned by introduction of free maternity services in all public hospitals in Kenya. These findings compare with findings on a study on exemption policy in Ghana which confirmed that introduction of free delivery care policy is associated with an increase in facility deliveries [14].…”
Section: Discussionsupporting
confidence: 78%
“…Maternal health is part of the family health package and includes delivery of normal births [18,19]. There is evidence from a number of countries that materialization of those initiatives improved utilization of target services and had a positive impact on the rate of assisted deliveries and/or Cesarean sections [20][21][22].…”
Section: Introductionmentioning
confidence: 99%